Comparison of Air Pollution Measurement (Zuun Ail area) - B, Bulgansaikhan; S, Lodoisamba; D, Shagjjamba; G, Gerelmaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
Results of 2012-2013 PM2.5 and PM2.5-10 aerosol pollution study of Ulaanbaatar city, Mongolia is been presented. PM2.5 and PM2.5-10 aerosol fractions have been measured three times a week at the Zuun ail of Ulaanbaatar city. Weight of the samples and Black Carbon were determined at the Nuclear Research Center (NRC), National University of Mongolia. Element analyses have been performed at the NRC using XRF analysis. It includes Na, Mg, Al, Si, P,S, Cl, K,Ca, Ti, V,Cr,Co, Ni, Zn, Cu, As, Br, Sr, Ba, I, Hg, Pb. Average concentration of PM2.5-10 is 319 μg/m3, PM2.5 is 154 μg/m3 in the year.